Searching for a Bacteriophage Lysin to Treat Corynebacterium bovis in Immunocompromised Mice - Cheleuitte-Nieves, Christopher (Comp Med, 2020)
Corynebacterium bovis is the causative agent of Corynebacterium-associated hyperkeratosis in immunocompromised mice. The resulting skin pathology can be profound and can be associated with severe wasting, making the animals unsuitable for research. Although the administration of antibiotics is effective in resolving clinical symptoms, antibiotics do not eradicate the offending bacterium. Furthermore, antibiotic use may be contraindicated as it can affect tumor growth and is associated with Clostridioides difficile enterotoxemia in highly immunocompromised murine strains. Lysins, which are lytic enzymes obtained from bacteriophages, are novel antimicrobial agents for treating bacterial diseases. The advantage of lysins are its target specificity, with minimal off-target complications that could affect the host or the biology of the engrafted tumor. The aim of this study was to identify lysins active against C. bovis. Chemical activation of latent prophages by using mitomycin C in 3 C. bovis isolates did not cause bacteriophage induction as determined through plaque assays and transmission electron microscopy. As an alternative approach, 8 lysins associated with other bacterial species, including those from the closely related species C. falsenii, were tested for their lytic action against C. bovis but were unsuccessful. These findings were congruent with the previously reported genomic analysis of 21 C. bovis isolates, which failed to reveal bacteriophage sequences by using the PHAST and PHASTER web server tools. From these results, we suggest C. bovis is among those rare bacterial species devoid of lysogenic bacteriophages, thus making the identification of C. bovis-specific lysins more challenging. However, C. bovis may be a useful model organism for studying the effects of antiphage systems.